Survival benefit of radical prostatectomy in patients with advanced TURP-diagnosed prostate cancer: a population-based real-world study - Deng Lin; Le Lin; Liefu Ye; Tao Li; Yongbao Wei; Lizhi Li (BMC Surgery, 2024)
Abstract Objectives A considerable number of patients are diagnosed with prostate cancer (PCa) by transurethral resection of the prostate (TURP). We aimed to evaluate whether radical prostatectomy (RP) brings survival benefits for these patients, especially in the elderly with advanced PCa. Patients and methods We used the Surveillance, Epidemiology, and End Results (SEER) database to obtain PCa cases diagnosed with TURP. After the propensity matching score (PSM) for case matching, univariate, multivariate, and subgroup analyses were performed to investigate whether RP impacts the survival benefit. Results 4,677 cases diagnosed with PCa by TURP from 2010 to 2019 were obtained, including 1,313 RP patients and 3,364 patients with no RP (nRP). 9.6% of RP patients had advanced PCa. With or without PSM, cancer-specific mortality (CSM) and overall mortality (OM) were significantly reduced in the RP patients compared to the nRP patients, even for older (> 75 ys.) patients with advanced stages (all p < 0.05). Except for RP, younger age (≤ 75 ys.), being married, and earlier stage (localized) contributed to a significant reduction of CSM risk (all p < 0.05). These survival benefits had no significant differences among patients of different ages, married or single, and at different stages (all p for interaction > 0.05). Conclusions Based on this retrospective population-matched study, we first found that in patients diagnosed with PCa by TURP, RP treatment may lead to a survival benefit, especially a reduction in CSM, even in old aged patients (> 75 ys.) with advanced PCa.